Study of bacteria causing skin infections in school going children in Udupi district;cross-sectional study - K.L, Shobha; D'Souza, Jessica; C.N, Varun; Kumar, Vinod; Kamath, Ramachandra; L, Ramachandra (International Journal of Pharmacology and Toxicology, 2014)
Introduction: Skin infections are a common reason for consultation in primary care and in dermatology practice. The predominant strain causing infection varies by geographical location. The aim of our study was to evaluate various types of bacteria causing skin infections in school going children of Udupi district, Karnataka State, India. Materials and Methods: The study group consisted of school going 236 children in Udupi district. Consent was taken from the parents of respective children to screen for physical examination and to collect skin swabs. Skin swabs were collected from the site of lesions and processed for isolation and identification of the organisms. Antibacterial susceptibility testing was done by Kirby-Bauer disc diffusion test. Results: Swabs were collected from 53 children of 236 (22.45 %) who had abrasions or lesions on skin. Bacterial strains isolated were Staphylococcus aureus (13.2 %) Klebsiella species (1.88%). All the strains of Staphylococcus aureus were susceptible to Methicillin. Erythromycin resistance among these Staphylococcus aureus was 42.85% Discussion: Staphylococcus aureus, the pathogen isolated was 7 (87.5%), this study was in concordance with the study conducted by (Cassandra D. Salgado ET al.2003),who had reported Methicillin resistant strains of 1.3%.Our study did not find any Methicillin resistant Staphylococcus aureus. There was an increased resistance to the erythromycin. This was consistent with the data that had been established in many countries where erythromycin resistance was increasing in community acquired infections. Conclusion: Though Staphylococcus aureus was the common organism isolated from skin swabs, all were sensitive to methicillin,but high prevalence of erythromycin resistance of the Staphylococcus aureus in the community demands proper screening of the isolates for resistance in clinical settings.   Keywords: Staphylococcus aureus, Methicillin Sensitive, Skin Swabs, School Going Children.